MEMODERNISASI NEGERI DAN MENCIPTAKAN HARMONI: KOLABORASI MISIONARIS, PEMERINTAH KOLONIAL, DAN ELITE LOKAL DI POSO, 1892-1950 - Mohammad Sairin (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2022)
This article describes the process of modernization and harmony creation in Tanah Poso by missionaries and the colonial government involving local elites. So far Poso historiography states that the Poso area was relatively safe before the 1998 Poso conflict broke out. In fact, the Poso people in the pre-colonial period were always haunted by a fear of tribal wars and the tradition of headhunting which was the custom of the local community. The periodization of this study takes the period between 1892-1950. 1892 was the first year the missionary Albert Christiaan Kruyt arrived in Poso. At that time, he recorded war between tribes. Through an ethnographic approach and support from the Dutch East Indies government, the missionaries succeeded in 'modernizing' and creating harmony for the Poso people. This 'modernization' program also received support from Poso's local elite. This support even continued after the proclamation of Indonesian independence. Raja Poso Talasa welcomed the Netherlands Indie Civil Administration (NICA) and managed to prevent resistance against NICA in Poso. The speech by Lora Molindo, Poso's representative at the Malino Conference in 1946, also reflected the same wishes as other local elites. In 1950 colonial rule in Central Sulawesi officially ended with the dissolution of RIS.